2017
DOI: 10.1097/psy.0000000000000494
|View full text |Cite
|
Sign up to set email alerts
|

Surgically Induced Changes in Gut Microbiome and Hedonic Eating as Related to Weight Loss: Preliminary Findings in Obese Women Undergoing Bariatric Surgery

Abstract: Objective Weight-loss surgery results in significant changes in the anatomy, function and intraluminal environment of the gastrointestinal tract affecting the gut microbiome. While bariatric surgery results in sustained weight loss, decreased appetite and hedonic eating; it is unknown if the surgery-induced alterations in gut microbiota play a role in the observed changes in hedonic eating. We explored the following hypotheses 1) Laparoscopic sleeve gastrectomy results in changes in gut microbial composition ;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 53 publications
3
73
0
3
Order By: Relevance
“…The Damms‐Machado study, which undertook follow‐up sampling at 3 and 6 months, indicated that a number of butyrate‐producing species including Clostridium , Eubacterium , Faecalibacterium , Dorea and Coprococcus significantly declined post‐operatively with body weight changes positively correlating with Firmicutes numbers. Another study, demonstrated the differential abundance of four genera following surgery, a decrease in Bifidobacteriaceae was seen while an increase in Fusobacterium , Atopobium and Bulleidia were seen. The study by Liu et al did, however, report an increase in alpha‐diversity at 3 months following SG with a specific increase in Bacteroides thetaiotamicron associated with a decrease in BMI and circulating glutamate levels (Figure S1D).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The Damms‐Machado study, which undertook follow‐up sampling at 3 and 6 months, indicated that a number of butyrate‐producing species including Clostridium , Eubacterium , Faecalibacterium , Dorea and Coprococcus significantly declined post‐operatively with body weight changes positively correlating with Firmicutes numbers. Another study, demonstrated the differential abundance of four genera following surgery, a decrease in Bifidobacteriaceae was seen while an increase in Fusobacterium , Atopobium and Bulleidia were seen. The study by Liu et al did, however, report an increase in alpha‐diversity at 3 months following SG with a specific increase in Bacteroides thetaiotamicron associated with a decrease in BMI and circulating glutamate levels (Figure S1D).…”
Section: Resultsmentioning
confidence: 96%
“…The majority covered the impact of RYGB (n = 6). [78][79][80][81][82][83] Four studies assessed microbiota changes following SG and LSG 80,[84][85][86] ; one SG study 80 included RYGB as an additional group. The final study 87 looked at the impact of BIB ( Figure S1A).…”
Section: Impact Of Bariatric Surgical Procedures On the Gut Microbiotamentioning
confidence: 99%
“…Changes in gut microbiota composition are considered a potential contributor to the metabolic benefits of bariatric surgery (Basso et al, 2016;Liou et al, 2013;Sanmiguel et al, 2017). We investigated whether intestinal FGF15 modulates shifts in the microbial communities by VSG.…”
Section: Intestinal Fgf15 Modulates Microbiota In Cecal Contentmentioning
confidence: 99%
“…The lmfit function in R was used to perform a linear regression of each surrogate variable on the two explanatory variables -all surrogate variables were found to have p-value > 0.05 for the regression model fit. Principal component analysis was then performed on the R-log-transform of read counts in the individual biological replicates, using the R-log Transform function within the Deseq2 R package 5 . Surrogate variables were included as covariates in the linear model, resulting in a linear model with gene expression as output and input variables as control vs. injured, and 3 surrogate variables.…”
Section: Differential Gene Expressionmentioning
confidence: 99%